The Influence of Organizational Climate and Job Satisfaction on Teachers’ Work Stress in Private Islamic Schools - Mustika, Lutfia Richa Ayu; Megaputra, Yudhistira; Soedjono, Soedjono (Jurnal Paedagogy, 2025)
This study aims to analyze the influence of organizational climate and job satisfaction on teachers’ work stress in a private Islamic school in Pati Regency. A quantitative correlational approach with an ex post facto design was used. The population was 50 teachers at a private madrasah, and the entire population was sampled (saturated sampling). Data were collected via questionnaires and analyzed using SPSS version 26. Normality tests showed that the data were normally distributed. Multicollinearity and heteroskedasticity tests confirmed that the regression model met the classical assumptions. Pearson correlation results indicated significant negative relationships between organizational climate and work stress (r = -0.676, p < 0.01) and between job satisfaction and work stress (r = -0.596, p < 0.01). This suggests that the more positive the organizational climate and the higher the job satisfaction, the lower the teachers’ work stress tends to be. The study recommends improving the quality of the organizational climate and job satisfaction in order to reduce teacher work stress and create a healthier work environment in private madrasahs.